PENGARUH SUBSTITUSI IKAN TUNA (Thunnus sp) TERHADAP MUTU ORGANOLEPTIK DAN KIMIA ABON JANTUNG PISANG (Musa acuminate balbisiana colla) - dara, widia; Fanyalita, Antia (IAIN Batusangkar, 2017)
The purpose of this research is to know the making of shredded banana flower that has been boild and fried (abon) with an experiment of tuna substitution of 0%, 25%, 50% and 75% from weight of banana flower. The highest yield of 42% was obtained from the making of abon consisting of 25% banana flower and 75% tuna. The best result of organoleptic test result is D treatment (comparison of banana flower and tuna were 25%: 75%) in the likes category. Protein content increases with the increasing number of substitutes of tuna , otherwise the fiber content decreases. Fat content was between 18-20%. The most preferred abon chemical content (abon D) in every 100 g of abon contains 302 calories, 20.6% carbohydrate, 14.0% protein, 18.2% fat, ash content 4.2% and water content 42.9% and fiber 0.92 g. Abon D is made from 25% banana heart and 75% tuna meets SNI abon fish standard, except for the water content is still a bit high that is more than 10% of SNI standards.